Home-based care as an indispensable extension of professional care in ART - a plea for recognition and support - Hlope, Hlengiwe (Acta Academica: Critical views on society, culture and politics, 2006)
The Centre for Health Systems Research & Development is currently conducting a longitudinal study to assess the implementation of public sector anti-retroviral treatment (ART) in the Free State. Home-based care (HBC) is central in achieving good patient follow up, continuity of care and patient adherence to treatment. This paper considers the role of HBC in strengthening the ART programme and identifies barriers to effective HBC. To this end, group interviews were conducted with HBCs in the Free State. Problems in respect of training, resources, stipends, support, supervision and management were revealed. Amongst HBCs and primary health care nurses confusion occurred about HBCs’ roles and duties. It is recommended that gaps in policy implementation in respect of HBC should be addressed and that HBCs’ roles should be clarified.